2020
DOI: 10.1002/ppul.24963
|View full text |Cite
|
Sign up to set email alerts
|

Determination of tuberculin skin test for isoniazid prophylaxis in BCG vaccinated children who are using anti‐TNF agents for rheumatologic diseases

Abstract: Objective The use of tumor necrosis factor inhibitors (anti‐TNF) has a risk of activating latent tuberculosis infection (LTBI). This study was performed to investigate LTBI according to tuberculin skin test (TST) size and to determine the frequency of tuberculosis (TB) in bacillus Calmette‐Guerin (BCG)‐vaccinated children receiving anti‐TNF treatment for rheumatological disease. Materials and Methods The study consisted of 559 children. Information on demographics, anti‐TNF agents, TST size, and isoniazid (INH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…Likewise, limited studies in children, even in areas with an intermediate incidence of TB, indicated that biological agents did not v Tuberculosis in therapy with biological drugs significantly increase the risk of TB in children with juvenile idiopathic arthritis. 20,21 However, the majority of studies derive their results on a shorter period of follow-up. 22 All patients in the current study were followed for an average of more than three years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, limited studies in children, even in areas with an intermediate incidence of TB, indicated that biological agents did not v Tuberculosis in therapy with biological drugs significantly increase the risk of TB in children with juvenile idiopathic arthritis. 20,21 However, the majority of studies derive their results on a shorter period of follow-up. 22 All patients in the current study were followed for an average of more than three years.…”
Section: Discussionmentioning
confidence: 99%
“…Although the recommendations vary depending on the economic status and TB prevalence of a country, the TST, IGRA, or both, in combination with chest radiographs, are the approved LTBI screening procedures. 21,23,24 While the World Health Organization recommends TST or IGRA for LTBI screening, there is no gold standard for the LTBI diagnosis. 19 There are no well-designed randomized controlled trials in children examining the priority of TST or IGRA.…”
Section: Discussionmentioning
confidence: 99%